ETHICAL ARTIFICIAL INTELLIGENCE AND HUMAN RIGHTS: RISKS AND CHALLENGES - Oleg Pavenkov,; Vladimir Pavenkov,; Mariia Rubtcova, (PEOPLE: International Journal of Social Sciences, 2026)
As AI systems become increasingly pervasive in various aspects of everyday life, from social media algorithms to national security applications, the potential for both enhancing and violating human rights grows exponentially. Article argue that Artificial intelligence has revolutionized the way people live and work, transforming understanding of human rights and providing new opportunities for innovation. However, the widespread use of AI has also raised concerns about its impact on human rights. Normative ethics theories and principles AI impact’s ethical regulation on human rights were considered and discussed. The research paper examines human rights implications of AI and the ethical responsibility for harm caused by AI technologies. Different type of discrimination and biased behavior in artificial intelligence systems were observed. It is needed to consider legal and ethical liability for human right’s damage caused by AI technologies. The issue of legal and ethical liability for damage caused by artificial intelligence is becoming more important in the era of self-driving cars and robotic surgeons, as well as the use of artificial intelligence in traffic management, as errors made by artificial intelligence systems can lead to fatalities, as has already happened repeatedly. The article examines the complex interplay between AI advances and established human rights frameworks, with a particular focus on the problem of ethical aspects of implementation of social credit system. The article highlights the urgent need for global cooperation in developing comprehensive and adaptive philosophical, ethical and legal frameworks to protect human rights in the face of rapidly evolving AI technologies.